End-user preferences for plantain food products in Nigeria and implications for genetic improvement - Amah, D.; Stuart, E.; Mignouna, Djana B.; Swennen, Rony L.; Teeken, Béla (Wiley, 2021)
Plantain is an important food security crop for farming households in Nigeria. This study investigates the relative importance of plantain food products and their quality descriptors from the perspective of farmers in Southern‐Nigeria, to inform end‐user oriented and socially inclusive breeding strategies that drive hybrid adoption. Surveys were conducted in twelve rural communities in three states in the plantain belt of Nigeria, consisting of key informant interviews, sex‐disaggregated focused group discussions and individual interviews. Dodo (fried plantains), boli (roasted plantains), boiled plantain, plantain with beans and porridge were the most common food products identified in the study areas. Fruit size, pulp texture (firmness/softness), colour, maturity stage and taste were identified as the most critical characteristics, with impact on quality of processed food products. There were significant differences between states regarding the importance of plantain food products, but little interstate and gender differences for fresh fruit and food product quality characteristics.